2015
DOI: 10.1287/orsc.2015.1001
|View full text |Cite
|
Sign up to set email alerts
|

Risky Business: The Decline of Defined Benefit Pensions and Firms’ Shifting of Risk

Abstract: Since the early 1980s, employment in the United States has undergone significant transformation as the large corporations that once safeguarded employees with stable jobs and rewards for loyalty have replaced these employment relationships with ones based on cost containment and flexibility. One important consequence of these developments is that firms have abdicated their role as a critical risk bearer in society. Although evidence suggests that firms have increasingly shifted market risks onto their workforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 86 publications
(75 reference statements)
0
37
0
1
Order By: Relevance
“…Firms increasingly hire contract workers who receive no long-term job security, benefits, or often even training (Bidwell 2009, Bidwell & Briscoe 2009). Related trends include less opportunity for upward mobility (Bidwell & Mollick 2015), fewer institutional protections such as health and retirement benefits (Cobb 2015), and declining union membership ). The result is what Kalleberg (2009) refers to as precarious work, in which the power differentials between workers and employers are amplified.…”
Section: What Forces Are Fueling the Growth In Alternative Work Arranmentioning
confidence: 99%
“…Firms increasingly hire contract workers who receive no long-term job security, benefits, or often even training (Bidwell 2009, Bidwell & Briscoe 2009). Related trends include less opportunity for upward mobility (Bidwell & Mollick 2015), fewer institutional protections such as health and retirement benefits (Cobb 2015), and declining union membership ). The result is what Kalleberg (2009) refers to as precarious work, in which the power differentials between workers and employers are amplified.…”
Section: What Forces Are Fueling the Growth In Alternative Work Arranmentioning
confidence: 99%
“…For example, theories about the "base of the pyramid" postulate that companies can both increase profits and benefit the poor by creating products that are specifically tailored to the needs of low-income customers in developing countries (London & Hart, 2004;Prahalad, 2006). Here, given the increasing influence of investors (Cobb, 2015; Davis, 2009), we focus on whether theories on the CSP-CFP link change the practices of investors, shifting them toward socially responsible investing.…”
Section: Elaborating the Process Modelmentioning
confidence: 99%
“…Moreover, organizations increasingly resort to hiring contract workers who receive no long-term job security, benefits, or even adequate training (Bidwell and Briscoe, 2009). Likewise, various studies have shown how workers hired on temporary contracts encounter increased difficulties with upward mobility, receive fewer institutional protections (in the form of health and retirement packages) and as result, are more disfranchised from work, resulting in lower union membership (Bidwell et al, 2013;Cobb, 2015). Highlighting the precarity of these work arrangements, Sliter and Boyd (2014) show that part-time workers resort to moonlighting either to complement a low-paid job or because they cannot find full employment.…”
Section: Individuals Organizations and New Work Configurationsmentioning
confidence: 99%